Serum Annexin V and Anti-Annexin V levels and their relationship with metabolic parameters in patients with type 2 diabetes - Bilgir,Oktay (2019)
SUMMARY BACKGROUND We investigated the serum annexin V and anti-annexin V levels and their relationship with metabolic parameters in patients recently diagnosed type 2 diabetic. METHODS A total of 143 patients recently diagnosed type 2 diabetes and 133 control subjects were included in the study. Body mass index (BMI), hs-CRP, HOMA-IR, carotid intima-media thickness, and serum levels of annexin V and anti-annexin V were investigated. RESULTS HOMA-IR, serum hs-CRP, and carotid intima-media thickness were found to be statistically significant. The Pearson correlation analysis revealed a statistically significant positive relationship between the carotid intima-media thickness and the annexin V level (r=0.29, p=0.006*). A statistically significant positive relationship was also detected between the Annexin V level and level of serum hs-CRP (r=0.29 p=0.006*). CONCLUSION A positive relationship was observed between the carotid intima-media thickness and annexin V at the end of our investigation. In this regard, we also believe that serum levels of annexin V may be increased for cardiovascular protection in the elevation of carotid intima-media thickness.